Stones, bones, and the sacred : essays on material culture and ancient religion in honor of Dennis E. Smith - Cadwallader, Alan H.; Smith, Dennis E. (Dennis Edwin), 1944- (2016)
The world of early Christians was not a world lived in texts; it was a world saturated with material reality and concerns: what, where and when to eat or drink; how to present oneself in the space of bodily life and that of death; how to move from one place to another; what impacted status or the adjudication of legal charges. All these and more controlled so much of life in the ancient world. The Christians were not immune from the impact of these realities. Sometimes they absorbed their surrounds; sometimes they quite explicitly rejected the material practices bearing in on them; frequently they modified the practice and the rationale to create a significant Christian alternative. The collection of essays in this volume come from a range of international scholars who, for all their different interests and critical commitments, are yet united in treasuring research into the Greek and Roman worlds in which Christians sought to make their way. They offer these essays in honor of one who has made a lifetime's work in mining ancient material culture to extract nuggets of insight into early Christian dining practices--Dennis E. Smith. Features: Rich examples of method in the utilization of ancient material culture for biblical interpretation ; Thirteen essays with a response from Dennis E. Smith ; Maps, diagrams, and plates. (Publisher)
The scholarship of Dennis E. Smith / Hal E. Taussig -- Embodied inequalities : diet reconstruction and Christian origins / Steven J. Friesen -- Food crises in Corinth? Revisiting the evidence and its possible implications in reading 1 Cor 11:17-34 / Ma. Marilou S. Ibita -- Don't take it lying down : nondining features of the Omrit temple excavations / Daniel N. Schowalter -- Eating words in the New Testament / Keith Dyer -- Ancient drinking in modern Bible translation / Jorunn Økland -- Making men in Rev 2-3 : reading the seven messages in the Bath-gymnasiums of Asia Minor / Lynn R. Huber -- At the origins of Christian apologetic literature : the politics of patronage in Hadrianic Athens / William Rutherford -- One grave, two women, one man : complicating family life at Colossae / Alan H. Cadwallader -- The Corinthian [KAINAI KTISEIS]? Second Corinthians 5:17 and the Roman refoundation of Corinth / Dominika Kurek-Chomycz and Reimund Bieringer -- Women as leaders in the gatherings of early Christian communities : a sociohistorical analysis / Valeriy A. Alikin -- The political charges against Paul and Silas in Acts 17:6-7: Roman benefaction in Thessalonica / Jeffrey A.D. Weima -- Paul's walk to Assos : a hodological inquiry into its geography, archaeology, and purpose / Glen L. Thompson and Mark Wilson -- The Baptists of Corinth : Paul, the partisans of Apollos, and the history of baptism in nascent Christianity / Stephen J. Patterson -- A response / Dennis E. Smith
Includes bibliographical references and indexes
Keywords: Material culture -- Religious aspects -- Christianity; Christians -- Miscellanea; Church history -- Primitive and early church, ca. 30-600; Religion and politics; Religion and social problems; Religion, Prehistoric; Greece -- Religion; Rome -- Religion; Greece -- Antiquities; Rome -- Antiquities; Australian